Problems and needs when caring for stroke patient at homes - Uten Suten; Srimuang Paluangrit; Supika Dangkrajang; Wandee Sutthinarakorn; Vanida Prasert (Intelektual Pustaka Media Utama, 2022)
The Thailand health policy aim to develop the patient care system in a community level, especially, the home rehabilitation program for stroke patients. Currently, stroke patients have long term disabilities and recurrent stroke leading to the serious life-threatening and death. The study investigated the problems and needs of caregivers for taking care stroke patients after hospital discharge and caring at home. A qualitative study was conducted in 80 key informants that comprised of 25 post stroke patients, 25 caregivers, 10 local health care officers at the community, 10 community leader, and 10 health volunteers. An in-depth interviews and focus group discussions were designed to collect the data. Caregivers were not confident about ability and skill to care stokes patients at home. Additionally, they were not understood the policy and health care service system. Health volunteers lacked of experience for supporting stroke patients in the community. The community leader and local health care officer needed more knowledge and skills including budgets, equipment, and facilities for caring the stroke patients. Ability, knowledge, skill and experience for caring stoke patients of the health care team should be addressed. Moreover, resources, facilities, equipment and budgets must be properly supported.